P217 Current Practise in Considering Early Life Factors in Respiratory Disease: A British Thoracic Society Survey. (19th November 2012) - Bolton, CE; Bush, A; Hurst, JR; Kotecha, S; McGarvey, LP; Stocks, J; Walshaw, M
Abstract : Background: Despite an 8% UK preterm birth rate and the improved survival of very preterm infants into adulthood, we hypothesised that the longer term impact of early life factors on respiratory health and disease is not routinely considered by respiratory specialists. We surveyed BTS members to determine their practise. Methods: Using a survey link, an email was sent twice, 4 weeks apart, to clinically active BTS members, enquiring whether they asked their patients about birth-weight, being born preterm, pregnancy and postnatal complications, and time in a neonatal unit; whether patients' knew this information, and also whether members believed their patients had airflow limitation due to prematurity or low birth-weight. Results: There was good geographical spread of the 123 replies (61% consultants, 21% doctors in training, 15% nursing profession, 2% GPs and 1% SAS doctors). 93% worked in the secondary care sector (55% in teaching hospitals), and only 13 dealt predominantly with children (12 in hospital, 1 community). Results: are summarised in the Table . Only a small minority (mainly hospital paediatricians) ask "most respiratory patients" about early life factors. In those who do ask, there is a wide variation in patient knowledge, this being greatest for children, in whom parental recall or use of the "red book" assisted. Although 47% thought some of their patients were born preterm or had a low birth-weight, 46% were unaware and 7% thought there were none. Discussion: Given evidence suggesting early life factors do impact on respiratory health, the survey suggests little current consideration is given to these in adult medicine. Limited retrospective recall may preclude accurate assessment. To develop a greater understanding of the potential impact of early life influences on chronic respiratory disease requires a new approach, for example accessing early medical records, recall by a living parent of the patient or via a preterm registry. In tandem, training needs to address the gaps in history taking.